2014
DOI: 10.1016/j.jhep.2014.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Gli1 activation and protection against hepatic encephalopathy is suppressed by circulating transforming growth factor β1 in mice

Abstract: Background & Aims Hepatic encephalopathy (HE) is a neurologic disorder that develops during liver failure. Few studies exist investigating systemic-central signaling during HE outside of inflammatory signaling. The transcription factor Gli1, which can be modulated by hedgehog signaling or transforming growth factor β1 (TGFβ1) signaling, has been shown to be protective in various neuropathies. We measured Gli1 expression in brain tissues from mice and evaluated how circulating TGFβ1 and canonical hedgehog signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 37 publications
6
48
0
Order By: Relevance
“…These stages have been previously described in detail. 17 Expression of the bile acid transporter ASBT, the bile acid nuclear receptor FXR, and its cofactor SHP was significantly increased after AOM injection in the frontal cortex before the onset of neurological symptoms compared with control tissue ( Figure 5A and Supplemental Figure S1A), an effect that was observed through to major neurological decline. Interestingly, the expression of these key bile acid signaling components was dramatically decreased at the time of coma ( Figure 5A and Supplemental Figure S1A).…”
Section: Fxr Signaling In the Brain Is Up-regulated Following Acute Lmentioning
confidence: 97%
See 2 more Smart Citations
“…These stages have been previously described in detail. 17 Expression of the bile acid transporter ASBT, the bile acid nuclear receptor FXR, and its cofactor SHP was significantly increased after AOM injection in the frontal cortex before the onset of neurological symptoms compared with control tissue ( Figure 5A and Supplemental Figure S1A), an effect that was observed through to major neurological decline. Interestingly, the expression of these key bile acid signaling components was dramatically decreased at the time of coma ( Figure 5A and Supplemental Figure S1A).…”
Section: Fxr Signaling In the Brain Is Up-regulated Following Acute Lmentioning
confidence: 97%
“…17,18 Cerebral edema was assessed in all mice using the wet/dry weight method described by Baskaya et al 20 Water content was expressed as a percentage of brain weight, calculated as follows: ([wet weight À dry weight]/wet weight) Â 100%. Increased brain water content of 1% to 2% in mice is indicative of cerebral edema and is characterized by increased intracranial pressure.…”
Section: In Vivo Model Of Acute Liver Failurementioning
confidence: 99%
See 1 more Smart Citation
“…Speciically, TGFβ has both anti-inlammatory and proinlammatory efects on various immune cells in the body, including microglial activation. Increased levels of TGFβ have been demonstrated in the liver and serum in the AOM model of acute liver failure [38]. The authors demonstrated that peripheral TGFβ has implications on microglial activation [39].…”
Section: Proinlammatory Cytokinesmentioning
confidence: 99%
“…The authors demonstrated that peripheral TGFβ has implications on microglial activation [39]. Speciically, systemic treatment of mice with a neutralizing anti-TGFβ antibody, that did not signiicantly alter the underlying liver damage, but inhibited the actions of circulating TGFβ delayed the neurological decline observed in AOM-induced acute liver failure [38], and atenuated the morphological changes in Iba-1 positive microglia [39]. However, whether liver-derived TGFβ is acting directly on microglia to regulate the neuroinlammatory response in these models of HE, or whether the changes in microglial activation are an indirect efect of the protective efect of anti-TGFβ neutralizing antibodies remains to be established.…”
Section: Proinlammatory Cytokinesmentioning
confidence: 99%